Peningkatan Kemampuan Menulis Teks Eksplanasi Dengan Menggunaka Pendekatan CTL (Contextual Teaching and Learning) Siswa Kelas VIII.B MTs Negeri 2 Tana Toraja - Sri Fitriwati Andi Patangai (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research aims to describe the improvement of explanatory text writing skills using the CTL (contextual teaching and learning) approach in Class VIII.B students at MTs Negeri 2 Tana Toraja. Through the CTL (contextual teaching and learning) approach, improving explanatory text writing skills can be seen both in process and in product. This research was carried out in the stages of planning, action, observation and reflection. The results of this research show that the application of the CTL (contextual teaching and learning) approach can improve the skills of writing explanation texts in class VIII.B students at MTs Negeri 2 Tana Toraja, both in process and product. Process improvement is shown in student attitudes, student activities and the learning atmosphere, namely students participate actively in learning to write explanatory texts, students dare to express opinions during discussions, students can work together well in groups and students can follow and understand the steps of the CTL approach (contextual teaching and learning) well. Product improvements can be seen from the results of students' work. In cycle I, the average student score was 70.6 with 5 students or 20% of students completing the test. Furthermore, in cycle II the average student score increased to 84.35 with 17 students completing the test or 85% of students.